Methodology for sub-commercial calculation of the potential energy storage capacity of hydrogen, natural gas, and compressed air in salt caves - Câmara, R. (2020)
The incorporation of renewable energy into the future world energy matrix challenges its efficient use because renewable energy is not always available due to its dependence on natural factors such as wind and sunlight. This work develops a new resource management system to evaluate the renewable energy resources stored in salt caves using power-to-gas (P2G) and compressed air energy storage (CAES) technologies in the initial phase of a project (sub-commercial phase). To fulfill this objective, bibliographical research, document analysis, and consultations with specialists were used as the methodological basis. Two systems were identified to be used as a reference for the proposed methodology: Petroleum Resources Management System (PRMS) and CO2 Storage Resources Management System (SRMS). A classification framework is proposed for energy storage and an application of the framework is presented for a case study in Portugal. Similar to these reference systems, a sub-commercial project momentum was established, and three stages called total potential resource (R3), total probable resource (R2), and total proved resource (R1) were defined. The results support corporate and governmental decision-making on project continuity for both the market and governments, thus demonstrating their importance in new global energy reality. It is recommended to define the sub-commercial stage as well as the mapping ofR2 in the Brazilian territory as was done recently in Europe.